Modeling of cracking during pultrusion of large-size profiles. (1st March 2020) - Safonov, Alexander; Gusev, Mikhail; Saratov, Anton; Konstantinov, Alexander; Sergeichev, Ivan; Konev, Stepan; Gusev, Sergey; Akhatov, Iskander
Abstract: The pultrusion of large-diameter glass fiber reinforced epoxy rods at high pulling speed is often accompanied by the formation of cracks at the surface of a profile, leading to product rejection. In this study, we investigate the causes of crack formation based on numerical simulations of manufacturing process mechanics, including the temperature distribution, degree of polymerization, and residual stresses. Based on the built model, we solve the problem of temperature condition optimization for maximizing pulling speed. The results show that up to 27% increases in pulling speed are possible provided that the following conditions are met: thermal destruction of the material is avoided; a profile is cooled sufficiently quickly before cut-off; a high degree of polymerization is achieved in a final product; and there are no cracks in a profile.